2020
DOI: 10.3390/biom10040568
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Dependence of Cancer

Abstract: Tumorigenesis is accompanied by the reprogramming of cellular metabolism. The shift from oxidative phosphorylation to predominantly glycolytic pathways to support rapid growth is well known and is often referred to as the Warburg effect. However, other metabolic changes and acquired needs that distinguish cancer cells from normal cells have also been discovered. The dependence of cancer cells on exogenous methionine is one of them and is known as methionine dependence or the Hoffman effect. This phenomenon des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 78 publications
2
115
0
1
Order By: Relevance
“…This was confirmed by Judde et al when it was demonstrated that overall transmethylation was strongly reduced in methionine-independent revertants derived from the methionine-addicted cancer cells (12, 13). The phenomenon of methionine-addicted cancer cells was later termed the Hoffman-effect (9).…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by Judde et al when it was demonstrated that overall transmethylation was strongly reduced in methionine-independent revertants derived from the methionine-addicted cancer cells (12, 13). The phenomenon of methionine-addicted cancer cells was later termed the Hoffman-effect (9).…”
Section: Discussionmentioning
confidence: 99%
“…This arrest can be induced in mammalian and yeast cells by SAM limitation or methionine depletion. Cells show robust arrest in the G1 phase of the cell cycle due to the lack of stable pre-replication (pre-RC) complexes to initiate the S phase and a delay in G2/M is also observed [ 29 ]. The metabolic profiles resulting from DT8-treated cell lysates showed methionine depletion, which could, at least in part, explain the effect of the new biphenyl nicotinamide derivative DT8 ( 3 ) on cell cycle where it induced a blockade in the G1 phase at low doses and a delay in the G2/M phases.…”
Section: Discussionmentioning
confidence: 99%
“…The large overlap in the MCF-7 metabolic profiles of DT-8 and VIN, when compared with K, would suggest a similar mechanism of action but, as above observed, it is likely that DT-8 acts preferentially with respect to VIN, by mechanisms related to methionine depletion or S -adenosylmethionine (SAM) limitation, which, on the other hand, should be well associated with the cell cycle alterations observed with the DT-8 through a block in phase G1 at low doses [ 8 ]. The role in the control of the cell cycle of methionine depletion and/or SAM limitation may be linked to the control of the pre-replication complex (pre-RC) associated with the cell division cycle 6 (Cdc6) protein [ 29 ]. The formation of the pre-RC complex during the G1 phase is essential for chromosome replication to occur only once per cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells show a higher demand for nutritional supplies and certain metabolites compared to normal cells [ 4 , 74 ]. As mentioned above, the methionine metabolism is tightly regulated and coupled to other metabolic cycles ( Figure 1 ).…”
Section: Methionine and Its Role In Cancermentioning
confidence: 99%